Recovery of Dissolved Methane From Anaerobic Membrane Bioreactor Using Degassing Membrane Contactors - Velasco, Perlie; Jegatheesan, Veeriah; Othman, Maazuza (Frontiers in Environmental Science, 2018)
At present, the recovery and utilization of methane from anaerobic wastewater treatment systems as a source of energy are well researched and widely adopted for a more sustainable system approach. However, not all methane produced in an anaerobic treatment system is completely recovered; subsequently, dissolved methane present in the effluent can be released into the environment and contribute to greenhouse gas accumulation in the atmosphere and reduce the system’s methane yield. Many studies have already investigated and discussed the factors affecting the production of dissolved methane, as well as the techniques for its recovery. Among the recovery techniques, the use of degassing membrane contactor is most preferred for wastewater treatment application. However, reported data in the literature is limited to certain types of wastewater characteristics and anaerobic systems. Studies on membrane-based recovery of dissolved methane from AnMBR effluents are reviewed in this paper. For the case of the degassing membrane contactor, porous or micro-porous membranes provides higher dissolved methane recovery efficiency than non-porous. However, porous membranes are more susceptible to pore wetting problem. Among the different operating conditions of degassing membrane contactors, liquid velocity or flow rate greatly affects the recovery, wherein higher velocity decreases the recovery efficiency of dissolved methane. Consequently, research priorities aimed at development of degassing membrane to accommodate higher liquid velocity and to reduce pore wetting. Moreover, energy analysis of the AnMBR with degassing membrane system should be analyzed for performance in full-scale applications.